Congestion control using dynamic routing and flow control in store-and-forward computer networks. - Chouikha, Wahida. (University of Ottawa (Canada), 1991)
In this thesis, the problem of congestion control in computer communication networks is studied. The method employed consists of a combination of a dynamic routing policy that minimizes the delay, and buffer management schemes to control the flow of data. These schemes include (1) Complete Sharing, (2) Square Root Sharing, and (3) Sharing with Minimum Allocation. A dynamic model for a computer queueing network with finite buffer size, stochastic input and random channel errors, is used. Simulations using linear programming have been carried out on a simple 3-node network, under balanced and unbalanced traffic conditions. The important performance measures such as average delay, average throughput, the number of packets lost due to limitation in the buffer size, the total queues and the total external arrivals, are obtained from the simulation and compared. The relative merits and drawbacks of each approach are discussed.
Keywords: Engineering, Electronics and Electrical.